2018
DOI: 10.18517/ijaseit.8.6.7257
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Ecological Changes and Livelihood Dilemma of the Rural Household around the Oil Palm Plantation

Abstract: The pressure of global market demand for palm oil is driving a massive expansion of oil palm plantations in Indonesia. Although it provides benefits in economic terms, it also has social and environmental impacts. The impact is in the form of changes in the ecological landscape, conversion of agricultural land, rural household livelihood systems, reduced biodiversity, deformation, plant monoculturalization, and even a monostructuring of livelihood. This study aimed to provide an overview of changes in the ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Economically, the shift of these farmers provides quite good benefits, as research conducted in Pasangkayu Regency showed a better income difference after converting agricultural land into oil palm plantations [5]. However, this land conversion impacts the reduction of agricultural food land and creates a livelihood system dilemma in several villages [9] and forces households to adopt specific livelihood strategies in dealing with changing ecological conditions [10].…”
Section: Impact Of Land Use Changesmentioning
confidence: 99%
“…Economically, the shift of these farmers provides quite good benefits, as research conducted in Pasangkayu Regency showed a better income difference after converting agricultural land into oil palm plantations [5]. However, this land conversion impacts the reduction of agricultural food land and creates a livelihood system dilemma in several villages [9] and forces households to adopt specific livelihood strategies in dealing with changing ecological conditions [10].…”
Section: Impact Of Land Use Changesmentioning
confidence: 99%